In vitro regeneration of Arisaema leschenaultii (Blume) using leaf explants - Vijayan, V.; Vijayakumar, K. K.; Nigesh, S. (Current Botany, 2024)
A standard in vitro regeneration protocol from leaf explants was developed for a potential medicinal plant Arisaema leschenaultii. Maximum callus induction (78%) was achieved on MS medium fortified with BAP (1.5 mg/L) and NAA (0.9 mg/L). The maximum percentage of shoot proliferation (75%) was attained on MS medium supplemented with 2.0 mg/L of BAP and 0.5 mg/L of GA3. The highest root induction (70%) was achieved on MS medium prepared with the combination of NAA (1.5 mg/L) and IBA (0.6 mg/L). The well-rooted plantlets that successfully followed acclimatization in the green house survived. The present efficient and optimized protocol provides mass propagation as well as the possibility of germplasm conservation for this study species.